HUBUNGAN PERAN DUKUNGAN KELUARGA TERHADAP KEMAMPUAN PEMENUHAN PERSONAL HYGIENE PADA LANSIA: THE RELATIONSHIP OF THE ROLE OF FAMILY SUPPORT TO PERSONAL HYGIENE FULFILLMENT ABILITY IN THE ELDERLY - Arni Safdiantina (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2021)
Personal hygiene comes from the Greek language which means personal which means individual and hygiene means healthy. Personal hygiene is an action taken to maintain the cleanliness and health of a person for physical and psychological well-being. The purpose of this study was to determine the relationship between family support for the elderly in fulfilling personal hygiene at Posyandu Mawar 03 Bojong Raya, West Jakarta. The research design used was a cross-sectional design. The sample amounted to 73 people and was taken by random sampling. Collecting data using a research instrument in the form of a questionnaire. This research was conducted at Posyandu Mawar 03 Bojong Raya, West Jakarta on August 22, 2017. Data analysis used univariate analysis in the form of frequency and proportion distribution and bivariate analysis in the form of two-proportion difference test (chi-square). From 73 respondents, the average result of the elderly having good family support was 61.6%, while the elderly who fulfilled personal hygiene were on average in the bad category as much as 60.3%. There is a significant relationship between family support and the fulfillment of personal hygiene in the elderly (p value = 0.01).